2016
DOI: 10.1016/j.childyouth.2016.09.010
|View full text |Cite
|
Sign up to set email alerts
|

Social gradients and participant characteristics in child behavior problem interventions

Abstract: In the present study, the scaling up of Parent Management Training, Oregon Model (PMTO) in Norway was examined by investigating how large-scale dissemination affected the composition of the target group and the service providers by comparing child behavioral outcomes in the effectiveness and dissemination phases of implementation. Despite the larger heterogeneity of the service providers and the intake characteristics of the target group, which are contrary to the expectations that were derived from the litera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
3

Year Published

2017
2017
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 139 publications
(171 reference statements)
0
6
0
3
Order By: Relevance
“…For example, a small Norwegian study combined two trials of another US programme, PMTO, and found no adverse equity effects. 46 Our findings are important for policymakers and commissioners needing to identify, fund, and target interventions for those who are most at risk, as well as practitioners recommending or delivering parenting programmes. The Incredible Years inter vention is clearly an effective strategy to reduce conduct problems in families facing social disadvantage.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…For example, a small Norwegian study combined two trials of another US programme, PMTO, and found no adverse equity effects. 46 Our findings are important for policymakers and commissioners needing to identify, fund, and target interventions for those who are most at risk, as well as practitioners recommending or delivering parenting programmes. The Incredible Years inter vention is clearly an effective strategy to reduce conduct problems in families facing social disadvantage.…”
Section: Discussionmentioning
confidence: 89%
“…45 Incredible Years has features that might enhance its effectiveness across social groups. Although the programme's content and principles are similar to those of other evidence-based parenting programmes derived from social learning theory (eg, Triple P and Parent Management Training-Oregon [PMTO]), 46,47 it has a particular focus on a collaborative delivery model. Thus, parenting goals and strategies are tailored to families' needs, whether these needs arise from child characteristics, culture, social disadvantage, or family values.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The GenerationPMTO participants statistically differed from the BPT participants as follows: GenerationPMTO parents had lower education levels, their children were a mean of 1.3 years older; and their children tended to have higher levels of behavior problems. In a comparison between participant characteristics in the BPT and GenerationPMTO interventions with the general population of Norwegian families with children, Tømmerås () found that families in both studies had markedly lower levels of social and economic resources; furthermore, 76.2% children in the samples scored above the population normed 25th percentile on the Eyberg Child Behavior Inventory, intensity scale. Thus, both samples contained participants with heightened levels of family social and child risk.…”
Section: Methodsmentioning
confidence: 99%
“…Kjøbli og medarbeidere (14) fant at depresjon, angst og psykisk stress kan gjøre det vanskeligere for mødrene å følge konkrete råd på kort sikt. Sosiale forskjeller som for eksempel boforhold og dårlig økonomi kan også vaere en sperre (15). Dette kan underbygge viktigheten av å komme tidlig inn og gi universelle tilbud før problemene har etablert seg.…”
Section: Trygghet I Foreldrerollenunclassified